The Study of Removal of Remazol Red with Biomaterial Paras Stone and Opuntia ficus-indica by Coagulation-Flocculation - Hulwati, Siti; Fardiyah, Qonitah; Rumhayati, Barlah; Anggraini, Vita Dwi (Indonesian Journal of Chemistry, 2025)
The rapid progress of the textile industry sector has an impact on the environment by producing dye waste. The use of synthetic coagulants in processing textile industry waste containing azo dyes can cause residues that are detrimental to the environment. In this research, a technique for processing azo dye was done using natural coagulants. The use of natural coagulants provides several advantages, such as being eco-friendly, abundant, and cost-efficient. The potential of paras stone and Opuntia ficus-indica biomaterials as natural coagulants and flocculants for removing remazol red dye was thoroughly investigated under various conditions, including coagulant dose, the speed of coagulation, and the optimal initial pH of the test solution. The removal of remazol red dye was quantitatively analyzed using a UV-vis spectrophotometer at a wavelength of 520 nm. Findings from the research revealed that the removal efficiency of remazol red dye reached 96.70% with a coagulant dose of 2.75 g of paras stone and 2.00 g of O. ficus-indica at an optimal coagulation speed of 500 rpm and a pH of 4 for the testing solution. The results of this study provide an engineering perspective on optimizing operational parameters for removing remazol red in aquatic environments.